Research Priorities for the Conservation and Sustainable Governance of Andean Forest Landscapes - Mathez Stiefel, Sarah Lan (2017)
The long-Term survival of Andean forest landscapes (AFL) and of their capacity to contribute to sustainable development in a context of global change requires integrated adaptation and mitigation responses informed by a thorough understanding of the dynamic and complex interactions between their ecological and social components. This article proposes a research agenda that can help guide AFL research efforts for the next 15 years. The agenda was developed between July 2015 and June 2016 through a series of workshops in Ecuador, Peru, and Switzerland and involved 48 researchers and development experts working on AFL from different disciplinary perspectives. Based on our review of current research and identification of pressing challenges for the conservation and sustainable governance of AFL, we propose a conceptual framework that draws on sustainability sciences and social-ecological systems research, and we identify a set of high-priority research goals and objectives organized into 3 broad categories: systems knowledge, target knowledge, and transformation knowledge. This paper is intended to be a reference for a broad array of actors engaged in policy, research, and implementation in the Andean region. We hope it will trigger collaborative research initiatives for the continued conservation and sustainable governance of AFL.